Broad-Spectrum Light versus Blue Light for Phototherapy in Neonatal Hyperbilirubinemia: A Randomized Controlled Trial - Pratesi, Simone; Di Fabio, Sandra; Bresci, Cecilia; Di Natale, Cecilia; Bar, Shahar; Dani, Carlo (American Journal of Perinatology, 2015)
Phototherapy is standard care for treatment of neonatal hyperbilirubinemia. Our aim was to compare the effectiveness of broad-spectrum light (BSL) to that of blue light emitting diodes (LED) phototherapy for the treatment of jaundiced late preterm and term infants. Infants with gestational age from 35+0 to 41+6 weeks of gestation and nonhemolytic hyperbilirubinemia were randomized to treatment with BSL phototherapy or blue LED phototherapy. A total of 20 infants were included in the blue LED phototherapy group and 20 in the BSL phototherapy group. The duration of phototherapy was lower in the BSL than in the blue LED phototherapy group (15.8 ± 4.9 vs. 20.6 ± 6.0 hours; p = 0.009), and infants in the former group had a lower probability (p = 0.015) of remaining in phototherapy than infants in the latter. We concluded that BSL phototherapy is more effective than blue LED phototherapy for the treatment of hyperbilirubinemia in late preterm and term infants. Our data suggest that these results are not due to the different irradiance of the two phototherapy systems, but probably depend on their different peak light emissions.
Keywords: neonatal hyperbilirubinemia; phototherapy; jaundice; infant